Towards a Better Understanding of Agile Mindset by Using Principles of Agile Methods - Ozkan, Necmettin; Gök, Mehmet Şahin; Ozdenizci Kose, Büşra (Institute of Electrical and Electronics Engineers Inc., 2020)
The right way to agility should start with a proper agile mindset instead of applying Agile methods directly. However, apart from the manifesto, it is unlikely to find a comprehensive set of Agile principles that can serve for an improved agile mindset. Our study intends to fulfill this gap in a systematic way: providing a list of the Agile methods along with their principles within a single source, in the way of providing a better understanding of the concept of agility from a wide and exhaustive perspective. To do so, the collected 105 principles were content-analyzed in order to group them into 32 categories for a higher-level abstraction. These categories then were subsumed into two main categories. The whole grouping process was reviewed by one expert and the list was adjusted accordingly. Then, based on the consolidated list of the categorized principles, analysis and evaluations were made by the authors. As a part of the evaluations, semi-structured interviews with two experts were conducted to evaluate the categorized principles in general, especially in terms of their contribution to agility. © 2021 Elsevier B.V., All rights reserved.
15th Federated Conference on Computer Science and Information Systems, FedCSIS 2020 -- Virtual, Sofia -- 164056
Keywords: agile frameworks; agile methods; agile mindset; agility; principles